Is there a perfect protocol for patients with low ovarian reserve: a retrospective study comparing antagonist or agonist protocol in patients with low ovarian reserve - Rai, Seema; Khandavalli, Yasaswi; Lodha, Rama S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The high prevalence of infertility has made it a major healthcare problem in the present era. A majority of patients presenting with infertility have poor ovarian reserve (POR). Patients with POR are challenging to treat due to reduced treatment success and high cycle cancellation rate as there is no uniform definition and treatment protocol for these patients. The present retrospective study was performed to compare the pregnancy outcome between a long agonist protocol and flexible antagonist protocol in patients with POR. Patients with AMH ≤1.5 ng/mL and AFC ≤4 was included in the study. Controlled ovarian hyperstimulation is the basis of any in vitro fertilisation (IVF) procedure. There is no universally accepted ideal stimulation protocol for patients with POR, and it remains a challenge. Methods: This was a retrospective study covering the period from May 2019 to March 2020. Ninety-nine patients with low ovarian reserve (AMH ≤1.5 ng/mL and AFC ≤4) were included in the study. The patients underwent GnRH agonist/GnRH antagonist stimulation protocol using recombinant FSH. Demographic characteristics like age, BMI, duration of infertility was comparable. Total days of stimulation, total Gonadotropin dose used and clinical pregnancy rate in both the protocols was analyzed. Difference between the two groups was considered statistically significant at p-value <0.05. Results: Fifty-three patients underwent antagonist stimulation protocol and forty-six long agonist protocol. The clinical pregnancy rate was 37.7% (20/53) and 32.6% (15/46) in antagonist and agonist protocol respectively (p-value=0.5983). Pregnancy rate was higher in the antagonist group but the difference was not statistically significant. Conclusions: Antagonist protocol could marginally increase pregnancy rate in patients with low ovarian reserve. However, patients with poor ovarian reserve require a tailor-made protocol.